1979
DOI: 10.1508/cytologia.44.789
|View full text |Cite
|
Sign up to set email alerts
|

Banded Karyotypes of 11 Species of American Bats (<i>Genus Myotis</i>)

Abstract: The vespertilionid bat genus Myotis is among the most speciose of mammalian genera. It is comprised of some 68 species (Anderson and Jones 1967) and is found on virtually all major land masses of the world and in a wide variety of ecological situations. These bats are mostly insectivorous although at least one, Myotis (Pizonyx) vivesi, is a fish eater.Although there is a considerable volume of literature on the ecology, natural history, and behavior of the members of this genus, the systematic and phylogene ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…They studied a rather thorough taxonomic sample (primarily Old World members), including all putative subfamilies, and employed explicit methods for phylogenetic analysis. Furthermore, chiropteran karyotypes are conservative at the genus level and seem especially useful for inferring inter-generic relationships of bats (Baker, 1970;Bickham, 1979aBickham, , 1979bZima and Horáèek, 1985;Volleth and Heller, 1994b). Accordingly, others also have pointed to the study as positive evidence for including Miniopterus within Vespertilionidae (e.g., Simmons, 2000: 3334).…”
Section: Family Vespertilionidaementioning
confidence: 99%
See 1 more Smart Citation
“…They studied a rather thorough taxonomic sample (primarily Old World members), including all putative subfamilies, and employed explicit methods for phylogenetic analysis. Furthermore, chiropteran karyotypes are conservative at the genus level and seem especially useful for inferring inter-generic relationships of bats (Baker, 1970;Bickham, 1979aBickham, , 1979bZima and Horáèek, 1985;Volleth and Heller, 1994b). Accordingly, others also have pointed to the study as positive evidence for including Miniopterus within Vespertilionidae (e.g., Simmons, 2000: 3334).…”
Section: Family Vespertilionidaementioning
confidence: 99%
“…As a result, classical inferences of species relationships have been difficult. Karyotypic studies have been of little help as well because Myotis is one of the most karyotypically conservative genera within Vespertilionidae (2N = 44, FN = 5052;Bickham 1979aBickham , 1979bBickham et al, 1986;McBee et al, 1986).…”
Section: Subfamily Myotinaementioning
confidence: 99%
“…However, C-banding studies have demonstrated the presence of pericentromeric heterochromatic regions in most karyotypes of bat species analysed to date, with similar size to those described in most of the mammal species (Pathak et al, 1973;Bickham, 1979;Haiduk et al, 1981;Morielle-Versute et al, 1996;Santos and Souza, 1998;Volleth et al, 1999;Volleth et al, 2001).…”
Section: Genomic Content Of Satellite Dnamentioning
confidence: 61%
“…Extensive karyological analyses of Vespertilionidae species have been undertaken (Zima and Horacek 1985), with GTG-banding technique karyotypes available for most genera (Bickham 1979a, b, 1987, Zima 1982, Fedyk and Ruprecht 1983, Stock 1983, Harada 1988, Volleth and Tidemann 1989, 1991, Zima et al 1989, Volleth 1992, Volleth and Heller 1994, Volleth et al 2001, Kearney et al 2002. Some researchers have suggested the 2n=44 karyotype of genus Myotis as the ancestral vespertilionid karyotype based on fossil records and primitive morphology of the genus Myotis (Capanna and Civitelli 1970, Andō et al 1977, Bickham 1979b, Baker et al 1985, Zima 1982.…”
Section: Resultsmentioning
confidence: 99%
“…Others have preferred a 2n=50 ancestral karyotype similar to the genus Eptesicus karyotype that consists of acrocentric autosomes (Fedyk andRuprecht 1983, Stock 1983). GTGbanding comparisons have suggested chromosomal homologies among various species of the family Vespertilionidae (Bickham 1979a, b, 1987, Baker et al 1985, Volleth and Heller 1994, Volleth et al 2001. Robertsonian fusions or centric fusions are proposed as the major chromosomal rearrangements that have occurred during the karyotype evolution of the vespertilionid (Bickham 1979b, Baker et al 1985, Volleth and Heller 1994, Volleth et al 2001.…”
Section: Resultsmentioning
confidence: 99%